“I am not too old for training”: A qualitative study on the factors that encourage older workers’ participation in training - Sousa, I.C.; Amado, M. B. (7th Age in the Workplace Meeting, 2023)
The changing world of work imposes frequent changes to all individuals and requires workers to develop the tools to overcome the new challenges. Considering the high percentage of older individuals in the workforce (United Nations, 2019), it is crucial for organizations’ success to promote older workers’ opportunities to acquire new knowledge and update their professional skills through training (Beier et al., 2012). Organizations are thus called to adapt training to the specific needs of older workers so that they benefit from and return such investment (Callahan et al., 2003; Konings & Vanormelingen, 2015). The purpose of this study was to identify positive and negative characteristics in the design and implementation of training for older workers in order to encourage their effective participation in training. Previous research shows the positive effects of training on the performance of individuals and teams, such as increasing levels of self-efficacy, higher performance expectations, and better results (Aguinis & Kraiger, 2009). In a context of an aging workforce, appropriate learning and didactic strategies need to be implemented to encourage older workers participation (Ilmarinen, 2012). Although some investigation has been conducted (e.g., Liu et al., 2011), it is crucial to delve deeper into the topic, considering the recent changes that have taken place in the labor market, particularly those brought by the COVID-19 pandemic, and the heterogeneity of this age group. Twenty semi-structured individual interviews were conducted with participants aged between 50 and 66 years. Interviews were conducted between February and June 2022, both online and in-person. Data were subjected to content analysis, with categories defined a priori and a posteriori. Findings suggest the importance of deconstructing the narrative that older workers do not desire to participate in training due to their accumulated work experience and diverse knowledge. In fact, as there is a strong need for continuously acquiring and updating skills and knowledge, training is perceived as an important tool for motivating older workers and increase their sense of self-efficacy. However, the design of training should answer to the specific needs and preferences of this age group. The most important characteristic for participants was the applicability of training, i.e., the opportunity to use tools and knowledge acquired in training to perform their job. Theoretical and practical training, and the relevance of the topic were also frequently mentioned by participants as aspects that motivate their participation in training. The training schedule, which usually takes place after working hours, was the most mentioned negative characteristic of the training offered to participants. The second most mentioned negative aspect was the mandatory training. Organizations need to introduce flexibility in their training plans to allow individuals to decide on the location, time, modality, and topic of training (e.g., e-learning courses). Also, on-the-job training can be an attractive tool for transferring knowledge at work. Due to its exploratory qualitative nature, this study presents a small sample. Also, given the geographic distance between the researcher and some participants, some interviews had to be carried out online, while others were conducted in person.